The role of administrative districts in the administrative system of Serbia - Golić, Darko (Pravo, teorija i praksa, 2025)
This paper analyzes the role of administrative districts and local units of state administration authorities, as well as the needs and possibilities for their reform. The non-central aspect of public administration itself constitutes a complex whole with multiple distinct elements, interrelations, and needs. In this context, the paper examines the possibilities and methods for "strengthening administrative districts" and "improving vertical and horizontal oversight in the execution of original and delegated tasks" at the non-central level, as defined by current planning documents. The core of this analysis is grounded in positive legal provisions, as well as strategic and planning documents in Serbia, accompanied by relevant comparative references. The main research dilemma concerns the limited possibilities for enhancing the performance of state administrative tasks through or within administrative districts. This limitation stems from the nature of the non-central aspect of public administration as a complex subsystem with two components: local self-government with its own original tasks (decentralized aspect), and local self-government with delegated tasks alongside local units of state administration authorities (more or less centralized aspect), which are interconnected through the administrative district.